The Substance of Dumping in HDI's Point of View, its Existence Towards Islamic Law - Muhammad Ali Adnan; Atika Sunarto (IHSA Institute, 2020)
This paper discusses the views of international trade law and Islamic law on dumping practices. Dumping is the activity of buying and selling products at below normal prices in countries aimed at exporters for the sole purpose of controlling international market share. Dumping is carried out with the aim of seizing international share by a country, so that this is a high case in international trade. It is a fact that Indonesia is in the top fifth place on dumping charges. Dumping is a trade practice that is dishonest, however dumping is in fact not prohibited in the provisions of the WTO. However, importing countries can apply anti-dumping duties that apply to the WTO for dumping products to prevent or reduce the effects of serious losses on domestic products which are considered substantial. Islam recognizes the term dumping by the term